Long-Acting Patient-Controlled Opioids Are Not Associated With More Postoperative Hypoxemia Than Short-Acting Patient-Controlled Opioids After Noncardiac Surgery: A Cohort Analysis. (December 2016) - Belcher, Allan W.; Khanna, Ashish K.; Leung, Steve; Naylor, Amanda J.; Hutcherson, Matthew T.; Nguyen, Bianka M.; Makarova, Natalya; Sessler, Daniel I.; Devereaux, P.J.; Saager, Leif
Abstract : BACKGROUND: Opioids can contribute to postoperative desaturation. Short-acting opioids, titrated to need, may cause less desaturation than longer-acting opioids. We thus tested the primary hypothesis that long-acting patient-controlled intravenous opioids are associated with more hypoxemia (defined as an integrated area under a postoperative oxyhemoglobin saturation of 95%) than short-acting opioids. METHODS: This analysis was a substudy of VISION, a prospective cohort study focused on perioperative cardiovascular events (NCT00512109). After excluding for predefined criteria, 191 patients were included in our final analysis, with 75 (39%) patients being given fentanyl (short-acting opioid group) and 116 (61%) patients being given morphine and/or hydromorphone (long-acting opioid group). The difference in the median areas under a postoperative oxyhemoglobin saturation of 95% between short-acting and long-acting opioids was compared using multivariable median quantile regression. RESULTS: The short-acting opioid median area under a postoperative oxyhemoglobin saturation of 95% per hour was 1.08 (q1, q3: 0.62, 2.26) %-h, whereas the long-acting opioid median was 1.28 (0.50, 2.23) %-h. No significant association was detected between long-acting and short-acting opioids and median area under a postoperative oxyhemoglobin saturation of 95% per hour ( P = .66) with estimated change in the medians of −0.14 (95% CI, −0.75, 0.47) %-h for the patients given long-acting versus short-acting IV patient-controlled analgesia opioids. CONCLUSIONS: Long-acting patient-controlled opioids were not associated with the increased hypoxemia during the first 2 postoperative days. Abstract : Published ahead of print September 7, 2016.